PENGARUH BIAYA PENDIDIKAN, PERSEPSI MAHASISWA, DAN PROMOSI TERHADAP KEPUTUSAN MAHASISWA MEMILIH PROGRAM STUDI AKUNTANSI (Studi Kasus Pada Mahasiswa UNISRI, USB, UNSA, dan UTP) - Manek, Maria Venty; Rispantyo, Rispantyo; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
TheepurposeeoffthisfstudyAwasAtoSdetermineEtheEeffectRofDtheDcost ofD education onNtheEdecision of studentsSto choose an accounting study program, the effect of students 'perceptions on students' decision to choose an accounting study program and the effect of promotion on the decision of students choosing an accounting study program.This study uses primary data from answers to questionnaires distributed to all 2019 accounting study program students at SlametRiyadi University in Surakarta, Setia Budi University, Surakarta University, and Tunas Pembangunan University. The sampling technique uses purposive sampling method. The result of T count 2,470 with p-value 0,016 < 0.05 means that there is a positive and significant influence on the cost of education (X1) on the decision of students to choose an accounting study program (Y). H acyl t-,699 with a p-value of 0,487 > 0.05 means that any negative effects and no significant student perceptions (X2) the decision of the students choose courses accounting (Y). H acyl t count 0,314 with a p-value of 0,008 < 0,05 means there is a positive and significant effect of the promotion (X3 ) against the decision of the students choose courses accounting (Y). F test results of 5,071 with a p-value of 0.003 < 0.05, which means that simultaneously variable education costs (X1), student perceptions (X2), and promotions (X3) have a significant effect on students' decision to choose an accounting study program (Y) . The determination test shows the value of Adjusted R Square 0,156 concluded that the student decision variable can be explained by the three independent variables namely education costs, student perceptions, and promotions because the remaining Adjusted R Square 15 (100%-15% = 85%) isSexplainedDbyD the causes -Dother causes Soutside theEVmodel.